A comparison of different digital storytelling media on the comprehension of Grade 1, Grade 2, and Grade 3 students - Crisostomo, Shelly Keene E..; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Storytelling is one of the earliest forms of teaching. It is an effective tool in imparting valuable lessons since it puts the concept of a more realistic context, enabling the students to understand the lessons better. This research mainly concentrated on determining the appropriate digital storytelling medium given the following options: audiobook, audio-visal and electronic text storytelling when it comes to gauging the comprehension of grade school students using the three level guides of comprehension. A quasi-experiment ws conducted to collect data for this study. Storytellig attributes that make the medium more appealing to the students were also taken into account. And lastly, the difficulties encountered when conducting the storytelling sessions was heeded.
Twenty four students' ages 6 to 9 years from Villagers Montessori College participated in this study. The students were divided according to their comprehension level to the three storytelling sessions wherein they were exposed to different storytelling media. One group were exposed to audiobook storytelling, the other to audio-visual storytelling and lastly, to electronic text.
The data gathered were tabulated and analyzed. T-test analysis was used to determine statistical differences between the results of the comprehension test from the three storytelling sessions. Analysis shows [there] is no significant statistical difference in comprehension results of each storytelling medium. Having limited number of respondents for the experimental study, the researcher concluded that the study was not conclusive, and did not completely prove the theoretical and conceptual framework of the study.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Digital storytelling; Childrens -- Books and reading; Comprehension in children; School libraries -- Philippines -- Quezon City